Fluorescence imaging of beta cell primary cilia - Li, Zipeng A.; Cho, Jung Hoon; Woodhams, Louis G.; Hughes, Jing W. (Frontiers in Endocrinology, 2022)
Primary cilia are slender cell-surface organelles that project into the intercellular space. In islets, primary cilia function as signaling hubs to coordinate hormone responses to external cues and to mediate paracrine crosstalk among islet cells. Ciliary distribution and morphology in the intact islet is best visualized by fluorescence microscopy, which reveals spatial and structural details that are important to their roles in islet function. Here we describe a number of optical imaging methods that we have developed and optimized for the study of both mouse and human islets, including conventional confocal imaging in fixed tissues as well as time-lapse microscopy to assess live cilia behavior. We demonstrate our ex vivo imaging protocol using live-cell cilia sensors to show that islet primary cilia possess active motility, which can be quantified using a custom mathematical cilia waveform analysis. We discuss limitations and untapped potential of current modalities in cilia imaging, new tools on the horizon, and functional implications of dynamic cilia behavior in controlling islet cell crosstalk and insulin secretion.